Effect of Methoprene on larval and cocoon weight, ovariole length, egg number and fecundity of Bombyx mori L - Magadum, S.B.; Hooli Μ.Α.; Magdum, V.B. (ENTOMOLOGIA HELLENICA, 1990)
The effect of Methoprene on larval and cocoon weight, ovariole length, egg number and fecundity of BombYx mori (Polyvoltine Pure Mysore breed) was studied. Methoprene at 2.75,4.0 and 8.0 pg!ml dilutions was topically applied/sprayed on silkworm larvae repeatedly at 36h in 3rd, 4th and 5th stadium, at 48h in 4th and 5th stadium and singly at 72h in 5th stadium. Of the various dosages used, the repeated applications of 2.75 pg/ml at 36h in 3rd, 4th and 5th stadium of silkworm larvae resulted in significant increase in larval weight, cocoon weight, ovariole length, ovariole egg number and fecundity when compared to untreated controls.